Direct formation of 4, 5-disubstituted carbazoles via regioselective dilithiation. Issue 59 (30th June 2021) - Pocock, Ian A.; Alotaibi, Alya M.; Jagdev, Kesar; Prior, Connor; Burgess, Gregory R.; Male, Louise; Grainger, Richard S.
Abstract : The simple combination of a bulky TIPS group on nitrogen and C–H activation using n BuLi–TMEDA allows direct functionalization of the hindered bay region of carbazole. Abstract : Carbazoles are widely exploited for their interesting photophysical and electronic properties, however bay (4, 5-) functionalization is challenging, and previously inaccessible through carbazole C–H activation. We report a simple methodology which introduces a range of versatile 4, 5-functionality, enabling the wider investigation of ring annulation and close proximity effects on carbazole properties.